Time-course analysis of end-tidal partial pressure of CO2 for predicting endurance performance: a preliminary study - Sakamoto, A.; Matsumoto, Y.; Naito, H. (The Journal of Physical Fitness and Sports Medicine, 2018)
[Aims] Minute ventilation (VE) is regulated by PaCO2, PaO2, H+, catecholamine etc. Particularly, a change in PaCO2 level immediately stimulates the ventilatory response. The ventilatory responsiveness to CO2 stimulus has been shown to diminish after endurance training. Therefore, we tested our hypothesis that the time-course changes of PETCO2 (indirect index of PaCO2) and VE during an incremental test would differ depending on endurance performance levels. [Methods] 13 long-distance (LD) runners (7 were Tokyo-Hakone Ekiden relay race runners or candidates) and 16 middledistance (MD) runners underwent an incremental treadmill run until volitional exhaustion. PETCO2, VE, respiratory rate (RR), expired tidal volume (TVE) and (VE) 2 were measured breath-by-breath and then averaged every 15 s. [Results] The traditional performance measures such as VE O2max, speed at VE O2max, all-out time and speed at all-out were greater for LD than MD runners (P=0.000- 0.044). LD runners also showed greater PETCO2 (P=0.029) and VEO2 (P<0.001), and lower VE (P<0.001) and VE/VEO2 (P<0.001) during the test compared to MD runners. The lower VE was due to lower TVE rather than RR. When LD runners were analyzed, the Ekiden runners or candidates showed greater PETCO2 (P<0.001) and lower VE (P=0.026) than the other LD runners, while the traditional performance measures or the rest of the respiratory parameters did not differ between the two. [Conclusion] Sustained lower VE despite higher PETCO2 (45-50 mmHg) during an incremental test may be indicative of capable distance-runners.